Islamic problem solving therapy for postpartum depression among Muslim postpartum women in Nigeria - Danasabe, Mahmood; Elias, Nadiyah (2017)
This research was aimed to compare the difference between conventional problem solving therapy and adapted Islamic problem solving therapy in decreasing postpartum depression and improving the problem solving ability among Muslim postpartum depressed women in Nigeria. Quasi-experimental pre-posttest design was adopted. The study employed systematic random sampling in data collection and 80 participants received six home-visits sessions of either conventional or Islamic problem solving therapy. Descriptive statistics and t-test via statistics package for social science were used for data analysis. The outcome of the research indicated that both the conventional and Islamic problem solving therapy were found significantly effective in reducing postpartum depression and improving the problem-solving ability. However, Islamic problem-solving therapy treatment was significantly more effective for reducing postpartum depression and the two maladaptive dimensions of impulsive-careless skill and avoidance skill. It was also more effective in increasing positive problem orientation, but not more effective than conventional problem solving therapy in decreasing the negative problem orientation and in increasing the rational problem-solving skill. Implications of this study will be of particular interest to clinical obstetrics and gynecology, psychiatrists, psychologist professionals, social workers as well as health-care institutions, government and health policy makers.